Intergenerational Transfers and Asset Inequality in Japan: Empirical Evidence from New Survey Data1. Issue 1 (March 2014) - Hamaaki, Junya; Hori, Masahiro; Murata, Keiko
<x xml:space="preserve">Abstract</x> This paper quantitatively examines the impact of intergenerational transfers on asset inequality among Japanese households. We estimate an intergenerational asset transfer function with various control variables, using a unique micro dataset taken from a survey conducted by the Economic and Social Research Institute, Cabinet Office. Employing three different models, a Tobit model, an interval regression model and an ordered probit model, to ensure that our results are independent of the specific econometric approach used, we investigate whether asset transfers received are correlated with households' financial strength. We find that higher income households are likely to receive larger asset transfers. However, the contribution of intergenerational transfers to asset inequality appears to be small.